2017
DOI: 10.1016/j.jgr.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Panax ginseng total protein promotes proliferation and secretion of collagen in NIH/3T3 cells by activating extracellular signal-related kinase pathway

Abstract: BackgroundRecently, protein from ginseng was studied and used for the treatment of several kinds of diseases. However, the effect of ginseng total protein (GTP) on proliferation and wound healing in fibroblast cells remains unclear.MethodsIn this study, cell viability was analyzed using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay. Cell cycle distribution was analyzed by flow cytometer. The levels of transforming growth factor β1, vascular endothelial growth factor, and collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 43 publications
2
14
0
Order By: Relevance
“…The Rb1 supplementation improved the blastocyst quality by anti‐apoptosis and induced pluripotency gene expressions. These effects of Rb1 on apoptosis and stem cell proliferation are similar to the results of previous studies 43‐45 . Ginseng can be converted into more easily absorbed ginsenoside after oral administration 46 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The Rb1 supplementation improved the blastocyst quality by anti‐apoptosis and induced pluripotency gene expressions. These effects of Rb1 on apoptosis and stem cell proliferation are similar to the results of previous studies 43‐45 . Ginseng can be converted into more easily absorbed ginsenoside after oral administration 46 .…”
Section: Discussionsupporting
confidence: 88%
“…These effects of Rb1 on apoptosis and stem cell proliferation are similar to the results of previous studies. [43][44][45] Ginseng can be converted into more easily absorbed ginsenoside after oral administration. 46…”
Section: Rb1 Improved In Vitro Development Of Ivf Embryosmentioning
confidence: 99%
“…The voucher specimen (2145) was conserved at the Herbarium of College of Science, Beihua University (Jilin province, China). GP was prepared by the same method in the published article of the same laboratory [24]. Fresh ginseng roots (1 kg) were cut into small slices and extracted twice with phosphate-buffered saline (PBS) at 4°C for 4 h. The supernatant was condensed with an ultrafiltration membrane (30 kDa) and the concentrated solution was separated with Sephadex G50, the purity of which reached 90.2%.…”
Section: Methodsmentioning
confidence: 99%
“…The root extracts of Panax ginseng have been shown to protect skin in C57BL mice from acute UVB irradiation [233] and significantly improve healing after laser burn injury and excisional wounding [221, 234, 235]. Studies demonstrate Panax ginseng extracts enhance keratinocyte migration [221, 236], as well as stimulate proliferation [237] and increase collagen synthesis in human dermal fibroblasts [238] in vitro . In addition, Choi demonstrated that the ginsenoside Rb2, isolated from Panax ginseng , induces the formation of the epidermis in raft culture via increased expression of epidermal growth factor and its receptor, fibronectin and its receptor, and keratin 5/14 and collagenase I [239], all of which have critical roles in wound healing.…”
Section: Traditional Use Of Medical Plants In Wound Healingmentioning
confidence: 99%